(untitled) (Revista Rupturas, 2018)
Water is the fundamental source that allows the reproduction of life on the planet, including human life. Because it is one of the common goods that are vital to humanity, everyone must be allowed access to it in sufficient quantity and quality for their well-being. But this definition is not hegemonic, but rather the subject of a dispute: on one hand, the appropriation of water governance as a commodity by corporations; and, on the other hand, the empowerment of civil society as common good. The result of this dispute will define the water availability for society and, consequently, conditions of a decent reproduction for society.